The Influence of Religion and Sex Education on Juvenile Delinquency in Medan City - Pasaribu, Munawir (International Journal of Educational Research & Social Sciences, 2022)
Juvenile delinquency is something that is often discussed in the community, where juvenile delinquency has a very large impact in the midst of society. For this reason, special attention is needed to minimize juvenile delinquency that occurs in the midst of society. This study aims to see the effect of Religion and Sex Education on Juvenile Delinquency. The sample used in this study were teenagers in the city of Medan, with a sample of 170 samples. The results obtained that simultaneously, religiosity and sex education can affect juvenile delinquency by 71%. From the results of the above discussion, it can be concluded that partially, the religiosity variable (X1) has an effect on juvenile delinquency (Y) by 58.6%, while the Sex Education variable (X2) can affect the juvenile delinquency variable (Y) by 27.7%.